2015
DOI: 10.1063/1.4921899
|View full text |Cite
|
Sign up to set email alerts
|

Heat transport by phonons and the generation of heat by fast phonon processes in ferroelastic materials

Abstract: Thermal conductivity of ferroelastic device materials can be reversibly controlled by strain. The nucleation and growth of twin boundaries reduces thermal conductivity if the heat flow is perpendicular to the twin wall. The twin walls act as phonon barriers whereby the thermal conductivity decreases linearly with the number of such phonon barriers. Ferroelastic materials also show elasto-caloric properties with a high frequency dynamics. The upper frequency limit is determined by heat generation on a time scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Several calculations indicate that ferroelectric and ferroelastic domain walls have a large effect on phonon transport, and hence heat flux [177][178][179][180][181]. For example, a single domain wall in lead titanate increases by up to 20% the thermal resistance of a bulk sample [180].…”
Section: Domain Walls As Phonon Filtersmentioning
confidence: 99%
“…Several calculations indicate that ferroelectric and ferroelastic domain walls have a large effect on phonon transport, and hence heat flux [177][178][179][180][181]. For example, a single domain wall in lead titanate increases by up to 20% the thermal resistance of a bulk sample [180].…”
Section: Domain Walls As Phonon Filtersmentioning
confidence: 99%
“…Here we will show that the nucleation and growth of twin boundaries reduces thermal conductivity if the heat flow is perpendicular to the twin walls, which act as phonon barriers. By using strain to manipulate the twin pattern, the thermal conductivity can be reversibly controlled [83].…”
Section: Strain-controlled Thermal Conductivity and Thermal Memorymentioning
confidence: 99%
“…[45][46][47] It has been demonstrated that inorganic ferroelastic materials can be utilized for thermal management applications. 44,[48][49][50] Sieradzki et al studied the changes in the thermal conductivity of Li 2 -TiGeO 5 ceramics in the ferroelastic phase transition or domain formation. 50 Wang et al reported the difference in thermal conductivity values of layered PdSe 2 before and aer ferroelastic phase transition by uniaxial compression and demonstrated that the high ratio of the switchable thermal conductivity value between the two phases could be utilized for exibility and thermal management.…”
Section: Introductionmentioning
confidence: 99%